2014
DOI: 10.1080/03650340.2013.871706
|View full text |Cite
|
Sign up to set email alerts
|

Soil test-based nutrient balancing improved crop productivity and rural livelihoods: case study from rainfed semi-arid tropics in Andhra Pradesh, India

Abstract: Widespread multinutrient deficiencies in the semi-arid tropics (SAT) are among major factors for large gaps between farmers' current crop yields and potential yields. In this study, we adopted a stratified soil sampling method to assess soil fertility-related constraints in farmers' fields in eight districts of Andhra Pradesh in the semi-arid tropics of India. Most of the fields across all eight districts were critical in sulfur (61%-98% deficient fields); and up to six districts each in boron (83%-98% deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…The results further show that the soil samples were low in organic C (hence in available N), and widely deficient in P, S, B and Zn, but the deficiency of K was of minor nature. These results are in accord with the results of soil analysis reported from other states of India including Andhra Pradesh, Rajasthan and Madhya Pradesh 8,[10][11][12][13] . In the semi-arid regions of sub-Saharan Africa, soil fertility has been mainly focused on organic matter and major nutrient management, and little research has been reported on the extent of deficiencies of secondary and micronutrients.…”
Section: Fertility Status Of Sat Soils: Some Resultssupporting
confidence: 82%
“…The results further show that the soil samples were low in organic C (hence in available N), and widely deficient in P, S, B and Zn, but the deficiency of K was of minor nature. These results are in accord with the results of soil analysis reported from other states of India including Andhra Pradesh, Rajasthan and Madhya Pradesh 8,[10][11][12][13] . In the semi-arid regions of sub-Saharan Africa, soil fertility has been mainly focused on organic matter and major nutrient management, and little research has been reported on the extent of deficiencies of secondary and micronutrients.…”
Section: Fertility Status Of Sat Soils: Some Resultssupporting
confidence: 82%
“…However, under improved practice, the percentage increment in crop yields was almost the same as during previous years. Thus soil testbased nutrient balancing not only enhances crop productivity but also adds to resilience-building of production systems 14,17 . The findings from the participatory trials demonstrated the need for adopting science-led improved crop management practices and soil test-based fertilizer management to boost productivity and improve livelihoods in the SAT.…”
Section: Soil Mapping-based Fertilizer Management and Crop Productivitymentioning
confidence: 99%
“…The characterization of fertility status of farmers' fields particularly in India, has indicated micro-, and secondary nutrient deficiencies of boron (B), zinc (Zn) and sulphur (S) in addition to nitrogen (N), phosphorus (P) and potassium (K). Such nutrient depletion is the chief biophysical factor limiting production [11][12][13][14][15][16][17][18] . Soil health is a pre-requisite to strengthen agro-based enterprises and may prove to be a very effective entry point intervention to quickly harness the productivity benefits while bringing on board the majority farmers to initiate the process of upgradation of dryland agriculture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land degradation due to soil fertility decline is a major hindrance in enhancing food production and realizing productivity potential. Due to prolonged nutrient mining, drylands are depleted not only in primary nutrients but also secondary and micro nutrients like sulphur, zinc, iron and boron [7][8][9][10][11][12]. The strategies to rejuvenate farm soil health through balancing the deficient micro and secondary nutrients along with primary nutrients have shown 20% to 70% higher food production [13][14][15][16].…”
mentioning
confidence: 99%